2000
DOI: 10.1108/09534810010378551
|View full text |Cite
|
Sign up to set email alerts
|

Fermenting change ‐ Capitalizing on the inherent change found in dynamic non‐linear (or complex) systems

Abstract: While there is no set definition of what constitutes “complexity,” some general classes of definitions have emerged across the writings of several fields of science. The basis for the classifications and a general definition used in this issue are presented. The papers of this issue are classified into the general categories and introduced to the reader.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…We propose to show that networks stem from agents' spontaneous adjustments, and are structures that emerge from their ever-changing interactions. The perspective that we present is thus close to that of social constructivist works which deal with self-organization (Drazin and Sandelands, 1992;Tsoukas, 1998;Beeson and Davis, 2000;Bergmann-Lichtenstein, 2000;Black, 2000;Fuchs, 2002) and close to works which address the role that knowledgeable agents play in network structures production (Kilduff et al, 2006;Sydow and Windeler, 1998).…”
Section: Introductionsupporting
confidence: 51%
“…We propose to show that networks stem from agents' spontaneous adjustments, and are structures that emerge from their ever-changing interactions. The perspective that we present is thus close to that of social constructivist works which deal with self-organization (Drazin and Sandelands, 1992;Tsoukas, 1998;Beeson and Davis, 2000;Bergmann-Lichtenstein, 2000;Black, 2000;Fuchs, 2002) and close to works which address the role that knowledgeable agents play in network structures production (Kilduff et al, 2006;Sydow and Windeler, 1998).…”
Section: Introductionsupporting
confidence: 51%
“…Complexity theories are increasingly being used by organization theorists and practitioners as a way of understanding and changing organizations (Bechtold, 1997; Black, 2000; Boje, 2000; Choi et al, 2001; Gilchrist, 2000; Lewis, 1994; Macbeth, 2002; Shelton and Darling, 2001; Stacey et al, 2002; Tetenbaum, 1998). Complexity theories come from the natural sciences, where they have shown that disequilibrium is a necessary condition for the growth of dynamic systems (Prigogine and Stengers, 1984).…”
Section: Newer Perspectives On Changementioning
confidence: 99%
“…A wide range of organisational theorists and practitioners have argued that organisations are complex, non-linear systems in which change emerges through a process of spontaneous selforganisation (Arndt and Bigelow, 2000;Burnes, 2014;Black, 2000;MacIntosh and MacLean, 2001;Stacey, 2003). These theorists argue that the best-run companies survive because they operate at the edge of chaos by relentlessly pursuing a path of continuous innovation brought about by a process that resembles self-organisation in nature (Brown and Eisenhardt, 1997;Burnes, 2005;Frederick, 1998).…”
Section: Discussion: Complexity Theories and Organizationsmentioning
confidence: 99%
“…Complexity theories are increasingly being seen by academics and practitioners as a way of understanding organizations and promoting organizational change (Black 2000;Boje and Wakefield, 2011;Burnes, 2014;Choi et al, 2001;Macbeth 2002;Seel, 2006). In the natural sciences, their proponents use complexity theories to argue that disequilibrium (chaos) is a necessary condition for the growth of dynamic systems, but that such systems are prevented from tearing themselves apart by the presence of simple order-generating rules (Gell-Mann 1994;Prigogine and Stengers 1984).…”
Section: Literary Praxiphorical Analysis: Using Science Fiction and Fmentioning
confidence: 99%